The Semantic Bridge: How AI Works with Medical Ontologies - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into healthcare promises a revolution in diagnostics, personalized medicine, and clinical efficiency. However, ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation